Mucoepidermoid carcinoma mimicking a mucocele: a case report highlighting the importance of microscopic analysis of oral lesions - Tamires Thadeu Coelho; Adriele Ferreira Gouvea; Ademar Takahama Jr; Danielle Resende Camisasca; Silvia Paula de Oliveira; Rebeca Souza Azevedo (Associação Brasileira de Odontologia, 2018)
Objective: the aim of this paper is to report a case of palatal Mucoepidermoid carcinoma (MEC) mimicking a mucocele, to highlight the main differential diagnoses, and to point out the need of a biopsy to establish the diagnosis even in a suspicion of benign reactive lesions. Case report: a female was referred to a stomatologist for evaluation of a palate swelling noticed about two months earlier. Physical exam revealed a painless translucent submucosal nodule, with an erythematous halo, in the right soft palate. Considering the clinical appearance, diagnostic hypothesis included mucocele and pleomorphic adenoma. An incisional biopsy was performed. Histological analysis of the specimen showed definitive diagnosis of low grade MEC. The case was managed through a complete surgical excision. Currently, she has been followed up without any signs of recurrence. Conclusion: early diagnosis of MEC may guide an adequate therapeutic management and, consequently, promote a favorable prognosis.